NT‐ProBNP and high‐sensitivity troponin T as screening tests for subclinical chronic heart failure in a general population - Maria Averina; Michael Stylidis; Jan Brox; Henrik Schirmer (ESC Heart Failure)
Abstract Aims The aim of this study was to establish age‐specific and sex‐specific cut‐off values for N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) and high‐sensitivity troponin T (hs‐troponin T) in healthy subjects and assess cardiac biomarkers as screening tools for subclinical heart failure (HF) in a general population. Methods and results Altogether, 1936 participants were randomly selected from the general population Tromsø 7 study in Northern Norway. Diagnostic accuracy (sensitivity, specificity, and negative and positive predictive value) of cardiac markers for echocardiographically defined subclinical HF was evaluated. The receiver‐operating characteristic analysis showed that areas under the curve were relatively low (under 0.75) for both NT‐proBNP and hs‐troponin T, suggesting that the diagnostic accuracy of these biomarkers for subclinical HF was not excellent, especially for mild forms of HF and younger age group 40–49 years. Sex‐specific and age‐specific cut‐offs for hs‐troponin T (99th percentiles) and NT‐proBNP (97.5th percentiles) were established in healthy subjects from the same general population. The sex‐specific and age‐specific cut‐offs for NT‐proBNP had higher specificity for subclinical HF compared with the previously established single cut‐off 125 pg/mL. Age‐specific cut‐off for hs‐troponin T (18 ng/L) for men ≥60 years had also higher specificity than the single cut‐off 14 ng/L. These cut‐offs had high specificity, but low sensitivity, that makes hs‐troponin T and NT‐proBNP good biomarkers to rule in HF in case of a positive test, but not good enough to rule out all unrecognized HF due to false negative results. Conclusions N‐terminal pro‐brain natriuretic peptide and hs‐troponin T are suboptimal screening tools for subclinical HF in a general population due to low sensitivity.